2021
DOI: 10.1088/1755-1315/674/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Myxobolus infection in koi fish (Cyprinus carpio) gill tissue from Land Pond, Nglegok, Blitar Regency

Abstract: Koi (Cyprinus carpio) hatchery and aquaculture sector is highly beneficial as it is one of the Indonesian and international superior commodity. However, Koi are susceptible to pests and diseases. One of the diseases is Myxobolusis which is caused by the Myxobolus sp. parasite. The clinical symptom of Myxobolusis are lumps (boils) on the gills and cloudy reddish fluid secretion similar to pus. This research aims to determine the infection profile of Myxobolus through histology observation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In June 2020, the koi production area in Blitar was attacked by a fish disease. Many studies reported that extreme parasites attacked the koi carp in Blitar ( Maftuch et al, 2018 ; Soelistyoadi et al, 2020 ; Yanuhar et al, 2021 ). Furthermore, the parasite case in Blitar caused mortality reaching 90% ( Yanuhar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In June 2020, the koi production area in Blitar was attacked by a fish disease. Many studies reported that extreme parasites attacked the koi carp in Blitar ( Maftuch et al, 2018 ; Soelistyoadi et al, 2020 ; Yanuhar et al, 2021 ). Furthermore, the parasite case in Blitar caused mortality reaching 90% ( Yanuhar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies reported that extreme parasites attacked the koi carp in Blitar ( Maftuch et al, 2018 ; Soelistyoadi et al, 2020 ; Yanuhar et al, 2021 ). Furthermore, the parasite case in Blitar caused mortality reaching 90% ( Yanuhar et al, 2021 ). The infected fish became weak, experienced less motion, pale color, decreased appetite, and mortality occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The Minapolitan program has been running in Blitar Regency since 2011, centered in Nglegok District. Blitar Regency is one of the centers of koi fish in Indonesia [2,3]. Koi fish farming in Blitar has been started in 1983 and has progressed and become a very promising new business area for fish cultivators and investors [4].…”
Section: Introductionmentioning
confidence: 99%
“…The high content of organic matter in the waters is still one of the crucial problems in koi fish cultivation. This condition is the main cause of pathogenic infection [2,15]. Especially attention to the importance of water quality in most farmer communities is still not enough.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation